PENGARUH STRUKTUR SUKUK, UMUR SUKUK, DAN STATUS JAMINAN SUKUK TERHADAP PERINGKAT SUKUK PADA PERUSAHAAN YANG TERDAFTAR DI DAFTAR EFEK SYARIAH - Reva Muzalifah; Aida Yulia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The purpose of this research is to examine the effect of independent variables on sukuk rating of companies listed in the List of Islamic Securities in the period of 2013-2016. Independent variables that used in this research are sukuk structure, maturity, and guarantee status. The selection of the sample is using a purposive sampling method and obtained a sample of 12 sukuk, the type of data used in this research is secondary data such as financial statements, annual reports and statistical data of sukuk. Data collection techniques used in this research is the documentation. Data analysis was conducted using the statistical analysis that is multiple linear analysis techniques Data processed by using program Econometric Views (EViews) version 9. The results of this study show that 52,73% dependent variable or sukuk rating can be explained by the three of independent variables. Simultaneously the three of independent variables have effect on sukuk rating. Partially, sukuk structure, maturity, and guarantee status have effect on sukuk rating.